Compêtencias de estudo no ensino superior: integração de dados qualitativos e de dados quantitativos na explicação do desempenho de excelência - Vasconcelos, Rosa (2012)
Higher Education has changed in the last decade and this has contributed to a diversification of social and cultural student´s origins. In this article we will analise some of the engineering student´s characteristics and outline a profile of the freshmen at the University of Minho. We will pay attention to the study and leisure habits, parent´s academic qualifications, entrance grade and literacy and numeracy abilities.